From Pharmacovigilance to Pharmacovigilance Planning-The System Building for Safe Medication - 王惠珀(Hui-Po Wang); 王群力(Chun-Li Wang); 余萬能(Wan-Neng Yu); 許淑慧(Shu-Hui Hsu); 黃育文(Yu-Wen Huang); 林玉玲(Yu-Ling Lin); 呂彥禮(Yen-Lih Leu); 李靜宜(Chin-Yi Lee) (Yàowu shi͡p︡in fenxi, 2007)
The concept of pharmacovigilance planning (PVP) was initiated by the International Conference on Harmonization (ICH) in 2004 and followed by the publication of Topic ICH E2E Guideline. However, the implementation of PVP in societies like Taiwan where irrational medication or co-medication of conventional medicine with complementary/alternative medicine (CAM) is prevalent, became a challenge. This report aimed to (1) introduce the concept of PVP and the importance of evidence-based justification of medicinal products for risk prevention and minimization, (2) summarize the scientific evidence regarding the sites and mechanisms of drug-drug or drug-CAM interactions along the biological processing of xenobiotics and identify potential risks in relation to co-medication of conventional medicine with CAM by reviewing literatures, (3) employ public information to analyze potential risk underlying irrational medication of registered medicine, registered traditional Chinese medicine (TCM) and un-registered CAM in Taiwan, and (4) address the importance of conceptual change from individual product-oriented pharmacovigilance to a proactive system-based risk management of pharmacovigilance planning.